Balancing purity, pragmatism and partnership in occupational therapy clinical research: trials and tribulations of recruiting for a multisite stroke trial - Codd, Yvonne; Stapleton, Tadhg (My University, 2025)
Purpose – The REfLECTS trial was a randomised controlled trial (RCT) testing effectiveness of mirror box therapy in upper limb rehabilitation among sub-acute stroke patients. REfLECTS was a large-scale, rigorously planned study; however, implementation was challenging due to low recruitment rates, 803 patients were screened and only 26 were recruited. The purpose of this study is to explore factors and challenges influencing the recruitment of participants to this multisite RCT. Design/methodology/approach – A Communities of Practice (CoP) approach was used. Bi-monthly steering meetings were held to address recruitment issues and a focus group was conducted post-recruitment to identify influencing factors. Data from meeting minutes and the focus group were amalgamated and analysed using thematic analysis. Findings – The trial team (n ¼ 14) comprising academics (n ¼ 5) and clinicians (n ¼ 9) contributed to the steering meetings. The focus group (n ¼ 9) included researchers (n ¼ 5) and clinicians (n ¼ 4). Two major themes were identified: impact of COVID-19, including shorter in-patient stays affecting trial recruitment and clinical trials (and tribulations) highlighting therapist-led dilemmas and patient-related factors leading to patients declining to participate. Research limitations/implications – The CoP identifies important contextual clinical service-based and therapist-led factors, which have pragmatic impacts on the design and implementation of high-quality occupational therapy clinical trials. High-quality occupational therapy evidence for stroke rehabilitation is essential, however, there is a need to critically reflect on how clinical research can best be implemented in clinical practice to ensure implementation and subsequent usability of findings. Provision of ongoing support for clinicians during trial implementation is essential to manage the therapist-led clinical dilemma. Originality/value – Good research helps us improve therapy, however, maintaining research purity in the pragmatic “real world” of stroke rehabilitation is challenging. Clinicians encounter ethical dilemmas with randomisation in high-quality clinical trial methodologies and this study identifies the need for ongoing trial implementation support to ensure clinician and patient engagement, enhance recruitment and maintain research integrity.
PUBLISHED
Keywords: Occupational therapy, Clinical intervention studies, Randomised controlled trials, Implementation of trial methodology, Future clinical trial design; Inclusive Society; CLINICAL-TRIAL METHODOLOGY; HEALTH SERVICES RESEARCH; Occupational Therapy; Stroke; Stroke rehabilitation; Chronic Health Condition; Physical disability; Stroke; Health